Dimensional crossover in ultracold Fermi gases from functional renormalisation - Faigle-Cedzich, Bruno M.; Pawlowski, Jan M.; Wetterich, Christof (Arxiv, 2019)
We investigate the dimensional crossover from three to two dimensions in an ultracold Fermi gas across the whole BCS-BEC crossover. Of particular interest is the strongly interacting regime as strong correlations are more pronounced in reduced dimensions. Our results are obtained from first principles within the framework of the functional renormalisation group (FRG). Here, the confinement of the transverse direction is imposed by means of periodic boundary conditions. We calculate the equation of state, the gap parameter at zero temperature and the superfluid transition temperature across a wide range of transversal confinement length scales. Particular emphasis is put on the determination of the finite temperature phase diagram for different confinement length scales. In the end, our results are compared with recent experimental observations and we discuss them in the context of other theoretical works.
Gesehen am 18.02.2020